The Influence of Thermal Comfort on the Quality of Life of Nursing Home Residents. Issue 13 (3rd August 2017) - Mendes, Ana; Papoila, Ana Luísa; Carreiro-Martins, Pedro; Aguiar, Lívia; Bonassi, Stefano; Caires, Iolanda; Palmeiro, Teresa; Ribeiro, Álvaro Silva; Neves, Paula; Pereira, Cristiana; Botelho, Amália; Neuparth, Nuno; et al.
ABSTRACT: Thermal comfort (TC) parameters were measured in 130 rooms from nursing homes (NH), following ISO 7730:2005 in order to evaluate the influence of winter season TC indices on quality of life (QoL) in older individuals. Mean radiant temperature (mrT), predicted mean vote (PMV) and predicted percent of dissatisfied people (PPD) indices, and the respective measurement uncertainties were calculated using Monte Carlo Method. The WHOQOL-BREF questionnaire was conducted from September 2012 to April 2013, during the winter season TC sampling campaign. Winter PMV and PPD indices showed significant differences between seasons in median values for comfort. There were also significant differences between seasons for air temperature, air velocity, mrT, and relative humidity. The winter PMV index displayed a "slightly cool" [≤−1] to "cool" [≤−2] in thermal sensation scale [−3 to 3]. PPD index reflected this discomfort as evidenced by a high rate of predicted dissatisfied occupants (64%). The influence of winter season TC on older individual QoL results demonstrated that values of PMV above −0.7 had higher mean score of QoL (coefficient estimate: 11.13 units) compared with values of PMV below −0.7. These ﬁndings are of relevance to public health and may be useful for understanding NH indoor environment variables thus implementing preventive policies in terms of standards and guidelines for these susceptible populations.